Dietary Pattern and Nutritional Status of Child Labour at Dhaka City in Bangladesh (Bangladesh Journal of Nutrition, 2014)
A cross sectional study was conducted to observe the dietary pattern and nutritional status of a selected group of working children in Dhaka metropolitan city. The study was conducted on randomly selected 100 children from a school run by an NGO at Moghbazar in Dhaka engaged in child labor age ranging between 8 to 17 years. The socio-economic profile, anthropometric measurements and dietary pattern of children were assessed. Information on socio-economic conditions was collected by interviewing the respondents through questionnaire. Dietary intake of the respondents was collected by 24 hours recall method. While considering age, majority of the children (51%) belonged to the age group of of RDA. Both groups fulfilled the RDA of Niacin, Zinc and Iron. Boys fulfilled 91.1% of vitamin C, 88.9% of thiamine and only 38.9% of Riboflavin whereas; girls fulfilled 77.8%, 92.2% and 42.2% only of RDA respectively.Bangladesh J. Nutr. Vol. 26-27, December 2014, P: 61-74